Student employability examined from academic achievement and self-concept - Fatwa Tentama; Muhamad Hasan Abdillah (International Journal of Evaluation and Research in Education (IJERE), 2019)
Employability is a problem that often arises in its relation to job-seeking, where low employability has become an obstacle for individuals entering the workforce. Factors believed to influence levels of employability are academic achievements and self-concept. This study aimed to determine the relationship between academic achievement and self-concept with student employability. The subjects in this study were 85 students who were obtained through cluster random sampling. The research method used is a quantitative method, utilizing scales and report card scores as data collection tools. The scale used is scale of employability and self-concept. The data analysis used in this study is multiple linear regression analysis. The results of the data analysis showedsignificant relationship between academic achievement and self-concept with employability.